FORMULASI PEMBUATAN BISKUIT DENGAN SUBSTITUSI TEPUNG PISANG KEPOK TERMODIFIKASI (MUSA PARADISIACA) - Firdaus Syafii (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2022)
The aims of research was to make a biscuit formula substituted with modified kepok banana flour. There were four steps of research (modified banana flour, biscuit formulation, organoleptic analysis and physicochemical tests). The research design used a completely randomized design (CRD) with four factors which were F0 (0%), F1 (25%), F2 (50%), and F3 (75%). The parameters measured were organoleptic tests (taste, aroma, color, and texture). In addition, carried out physicochemical tests (moisture, resistant starch, starch digestibility, and total fiber) on the best formula. The results showed that the best formula was obtained in the F2 treatment which was 50% banana flour substituted biscuits. The selected cookies (F2) contained 4.35% moisture, 40.12% resistant starch, 35.24% starch digestibility, and 17.51% dietary fiber. The selected biscuit has good sensory quality and had met SNI standard. it can be used as a functional food and can be consumed especially to control the weight and people with diabetes mellitus.